Optoelectronic properties of tin-lead halide perovskites - Savill, KJ; Ulatowski, AM; Herz, LM (American Chemical Society, 2021)
Mixed tin–lead halide perovskites have recently emerged as highly promising materials for efficient single- and multi-junction photovoltaic devices. This Focus Review discusses the optoelectronic properties that underpin this performance, clearly differentiating between intrinsic and defect-mediated mechanisms. We show that from a fundamental perspective, increasing tin fraction may cause increases in attainable charge-carrier mobilities, decreases in exciton binding energies, and potentially a slowing of charge-carrier cooling, all beneficial for photovoltaic applications. We discuss the mechanisms leading to significant bandgap bowing along the tin–lead series, which enables attractive near-infrared bandgaps at intermediate tin content. However, tin-rich stoichiometries still suffer from tin oxidation and vacancy formation which often obscures the fundamentally achievable performance, causing high background hole densities, accelerating charge-carrier recombination, lowering charge-carrier mobilities, and blue-shifting absorption onsets through the Burstein–Moss effect. We evaluate impacts on photovoltaic device performance, and conclude with an outlook on remaining challenges and promising future directions in this area.